Host and Microbiome Genome-Wide Association Studies: Current State and Challenges - Awany, Denis; Allali, Imane; Dalvie, Shareefa; Hemmings, Sian; Mwaikono, Kilaza S.; Thomford, Nicholas E.; Gomez, Andres; Mulder, Nicola; Chimusa, Emile R. (Frontiers in Genetics, 2019)
The involvement of the microbiome in health and disease is well established. Microbiome genome-wide association studies (mGWAS) are used to elucidate the interaction of host genetic variation with the microbiome. The emergence of this relatively new field has been facilitated by the advent of next generation sequencing technologies that enable the investigation of the complex interaction between host genetics and microbial communities. In this paper, we review recent studies investigating host-microbiome interactions using mGWAS. Additionally, we highlight the marked disparity in the sampling population of mGWAS carried out to date and draw attention to the critical need for inclusion of diverse populations.